Konsep Guru Sebagai Profesi (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
Profession etymologically comes from the word profession (English) which comes from the Latin profess which means "capable or expert in work". A profession can be interpreted as a job or position that requires skills obtained through certain education and training according to special requirements, have certain responsibilities and codes of ethics. Teachers can be said to be a profession because not everyone can become a teacher, becoming a teacher must also go through formal education and training, and have a certain code of ethics. This research aims to understand more deeply the concept of teachers as a profession. The method used in this study uses qualitative research methods, in the form of literature studies. The results of this study include: (1) the concept of the profession (2) the concept of teachers as a profession (3) the role of teachers as a profession (4) teachers' rights (5) teachers' obligations (6) the challenges of professionalism of Indonesian teachers (7) the teacher's code of ethics.